Implementasi Model Pembelajaran Interaktif Untuk Meningkatkan Keterampilan Berpikir Kritis Dan Minat Belajar Siswa Sdn Kubang Apu - Nurma’ardi, Hilda Dhaniartika; Herdiansyah, Dhean; Hummairah, Salwa Tsabitah; Sunisti, Ayu (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
This research is motivated by the low critical thinking skills and learning interest of students due tothe lack of innovation in the use of learning media. Thus, the purpose of this study is to analyze the obstaclesand impacts of the minimal application of interactive learning media on students' learning interest andcritical thinking skills. This research was conducted at SDN Kubang Apu, where the subjects of the researchwere all fourth grade students at the elementary school. The type of research used is a descriptive qualitativeresearch method. The data collection technique was carried out through interviews, observations, anddocumentation. Based on the research results obtained, choosing learning media has a close relationshipwith student responses. So that optimizing the use of interactive learning media needs to be maximized inorder to attract student interest and provide a good learning impact. Packaging material in interestingcontent from interactive learning media can attract students' interest and activeness to be more focused, sothat students will be unconsciously challenged to be able to explore and criticize the presentation andproblems given in learning. The use of interactive learning media is certainly not free from obstacles, butthese obstacles can be overcome by maximizing the teacher's ability to explore its use and creation moreoptimally and regarding facilities, teachers can optimize the use of existing facilities that can be provided.Keywords: Interactive Learning Model, Critical Thinking Skills, Learning Interest